Bussines Model Canvas (BMC) dan Analisis SWOT Sebagai Strategi Pengembangan UMKM Sanggar Alam Batik Kecamatan Sukorejo Kabupaten Pasuruan - Sueb Sueb (Universitas Yudharta Pasuruan, 2023)
The research study to analyze the business model and development strategy of Sanggar Alam Batik Kec. Sukorejo Kab. Pasuruan based on BMC and SWOT analysis. This study uses a descriptive qualitative approach. Data was collected and then analyzed based on Business Model Canvas (BMC) analysis and SWOT analysis. BMC is used to describe Sanggar Alam Batik's business conditions, while SWOT analysis is used in the formulation of business development strategies that are applied to new business models. The results of research on applying the right strategy in business development at Sanggar Alam Batik are SO strategies which consist of 1) finding a strategic place and creating a batik gallery. 2) Create a website as a marketing medium and expand the network in various marketplaces and social media. 3) Expanding market share to the global market. While the adjustment of Sanggar Alam Batik's business model provides an overview of nine model blocks including 1) customer segment, 2) value proposition, 3) customer relationshiip, 4) channell, 5) revenue stream, 6) key resources, 7) key activities, 8) partnerships key, 9) a cost structure that is expected to be able to develop 1) service quality, 3) human resource competence, and 4) support the achievement of clearer targets. The results of the BMC and SWOT evaluations provide an illustration that Sanggar Alam Batik needs a strategy to improve its business by adding eight blocks, including 1) customer segment, 2) customer relationships, 3) channels, 4) revenue streams, 5) key resources, 6) key activities, 7) key partnerships, 8) cost structure